การศึกษาคุณภาพการจัดการเรียนการสอนในหมวดวิชาศึกษาทั่วไปของหลักสูตรปริญญาตรีวิทยาลัยเซนต์หลุยส์ - ชื่นบุญ, อัชฌา; สร้อยโมรี, พิศุลี; บุริมจิตต์, ทรงวุฒิ; รามสิทธิ์, ภาวดี; แสงดารารัตน์, ชุติมา; กาญจนทรางกู, วฤณดา; ช่องชนิล, นฤมล (Journal of Research and Curriculum Development, 2020)
The purposes of this research aimed to study in the quality of the instructional management of the courses of General Education for the Bachelor’s Degree Programs in Saint Louis College consists of 1) Learning outcomes 2) Course content 3) Design of teaching methods and teaching activities 4) Course assessment and evaluation. The sample involved 218 nursing students, 31 psychology students, and 57 physiotherapy students, collected using a questionnaire, and 23 nursing students, 20 psychology students, and 20 physiotherapy students, collected using focus group discussion. Data was analyzed by descriptive statistics and content analysis. The results indicated that the quality of the instructional management of the courses of General Education for the Bachelor’s Degree Programs in Saint Louis are in high levels; faculty of nursing with an average of 3.67, faculty of psychology with an average of 3.65, and faculty of physiotherapy with an average of 3.65. There were comments suggesting that the instructional management of the courses of General Education should design more courses focusing on the real-life situations and ways of living.